Google Classroom as a Tool for Improving Basic English Translation Competencies for Non-English Department Student - M. Ridhwan; Melda Yeni (Universitas Muhammadiyah Gresik, 2023)
This study aims to determine whether e-learning of Google Classroom can improve the basic English translation skills of PAI’s students STAI Auliaurrasyidin Tembilahan, as well as to determine their perception of use. The ability to translate is one of the important skills that must be mastered by students in the current era of globalization. However, many students face difficulties in understanding and transferring the meaning from English to Indonesian correctly. The CAR design (Classroom Action Research) was chosen for the design of this research. This study consisted of two cycles, each cycle involving planning, action, observation, and reflection stages. This research located at STAI Auliaurrasyidin Tembilahan, Indragiri Hilir Riau, 19 Participants of the third semester class III/B Department of Islamic Education (PAI) STAI Auliaurrasyidin Tembilahan during the Odd Academic Year 2021/2022. The Data were collected using test, observation, fieldnote, and questionnaire. A questionnaire was used to answer students' perception on google classroom and was adapted from the TAM (Technology Acceptance Model) model introduced by Davis in 1986. The data were analyzed quantitatively and qualitatively. The results showed that there were students’ improvements in basic English Translation. The pre-cycle